Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1002/ejlt.200800272
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of W1/O/W2 emulsions and droplet size distribution measurements by pulsed‐field gradient nuclear magnetic resonance (PFG‐NMR) technique

Abstract: manyMultiple emulsions of W 1 /O/W 2 type are of major interest in life sciences, offering possibilities for the encapsulation of water-soluble active agents. In food science, they are also applied for fat reduction. The droplet size distributions of the inner and outer emulsions are of main importance as they influence the rheological and sensorial properties, the release kinetics, as well as the structural and microbial stability. However, the determination of the inner and outer droplet size distributions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…39,40 This major caveat is probably why diffusion-diffractions are not observed in most diffusion NMR studies of neuronal tissue, 1,41,42 broadly distributed emulsions, [43][44][45][46] and other porous media which are characterized by a relatively broad size distribution. In fact, in a recent work, Pages et al 47 showed the reversible loss of diffusion-diffraction minima when RBCs transformed from discocytes ͑relatively monodispere͒ to spherocytes ͑broader size distribution͒.…”
mentioning
confidence: 99%
“…39,40 This major caveat is probably why diffusion-diffractions are not observed in most diffusion NMR studies of neuronal tissue, 1,41,42 broadly distributed emulsions, [43][44][45][46] and other porous media which are characterized by a relatively broad size distribution. In fact, in a recent work, Pages et al 47 showed the reversible loss of diffusion-diffraction minima when RBCs transformed from discocytes ͑relatively monodispere͒ to spherocytes ͑broader size distribution͒.…”
mentioning
confidence: 99%
“…9(a). At larger values, the steep decrease is diminished indicating that the two compartment limit is not fully reached, which is also reflected by the increase of d 33 with D (see also Wolf et al [89] ). The noise level has to be considered during fitting because of normalisation of the signal.…”
Section: Double Emulsionsmentioning
confidence: 90%
“…In 2009, the results were confirmed by applying PFG-STE to WOW-double emulsions produced in a two-step procedure. [89] At small g values deviating, but at higher gradient steps parallel signal attenuation of the double emulsion compared with the corresponding single emulsion was found. Molecular exchange between the inner and the outer water phase was supposed to be responsible for the observation.…”
Section: Double Emulsionsmentioning
confidence: 95%
“…In several publications, the possibility of molecular exchange in double emulsions is discussed [5][6][7][8][9][10][11][12] . In some publications [8][9][10] , a molecular exchange model was applied, which originally was found to be applicable in case of cellular systems [5][6][7] .…”
Section: Diffusion Phenomena Between W 1 and W 2 In W 1 /O/wmentioning
confidence: 99%
“…In some publications [8][9][10] , a molecular exchange model was applied, which originally was found to be applicable in case of cellular systems [5][6][7] . There is, however, some controversy whether such effects are observed or other phenomena are responsible for the experimental results.…”
Section: Diffusion Phenomena Between W 1 and W 2 In W 1 /O/wmentioning
confidence: 99%